Food security in Colombia: Associated factors, public policies and research opportunities - Vivanco Zuñiga, Karina; Montero Castillo, Piedad Margarita; Marrugo Ligardo, Yesid Alejandro (Revista de Ciencias Sociales, 2025)
Food security is a concern in Colombia since the availability, access, use, and stability of food directly affect the country’s development. Considering these elements, the objective of this research was to identify the main factors that cause food insecurity in Colombia, taking into account climate change, structural inequalities, the supply chain, and its distribution. The methodology used was documentary research, through a critical and exhaustive review of the existing literature. Among the main findings, it was highlighted that although there has been a gradual reduction in food insecurity, improvements have been halted, especially in rural and vulnerable sectors, linked to issues such as poor management of public policies, food losses in the supply chain, the effects of climate change, among others. It was concluded that guaranteeing food security in Colombia requires joint work, the reduction of poverty and social inequalities, and innovation to address the internal challenges facing the country.